Optimal operation of Hoa Binh reservoir for flood control on Hong-Thai Binh river system - Can, Ngo Huy; Don, Nguyen Thanh; Phong, Nguyen Hong; Anh, Nguyen Tuan; Que, Nguyen Van (Vietnam Journal of Mechanics, 2008)
In the paper the optimal operation of Hoabinh reservoir for flood control on Hong–Thai Binh river system is presented. The findings show that in the flood season in 1996 if the operation of gates and outlets of Hoa Binh reservoir was made base on the calculated release, the water level at Hanoi would be 12.3 m and the water level of Hoa Binh reservoir would be 98 m. So the calculated release from Hoabinh reservoir in August 1996 can be considered as optimal in the mean that the water level at Hanoi can be controlled and the Hoabinh reservoir still have necessary pool for controlling the next floods